In Vivo Monitoring on Growth and Spread of Gray Leaf Spot Disease in Capsicum annuum Leaf Using Spectral Domain Optical Coherence Tomography. (19th January 2016) - Ravichandran, Naresh Kumar; Wijesinghe, Ruchire Eranga; Shirazi, Muhammad Faizan; Park, Kibeom; Lee, Seung-Yeol; Jung, Hee-Young; Jeon, Mansik; Kim, Jeehyun
Abstract : We have demonstrated the application of optical coherence tomography (OCT) in diagnosis of growth and spread of the gray leaf spot disease in Capsicum annuum leaf caused by the fungus Stemphylium lycopersici . Using 2D cross-sectional and 3D volumetric images of OCT, in vivo study of layer differences between fungus infected leaves and healthy leaves was observed with distinctive features. We observed that the internal layers of the disease-affected parts of the leaf seem to merge forming a single thick layer. The obtained OCT results verify the noninvasive diagnosis ability of fungal growth and spread in Capsicum annuum leaves and the applicability of this methodology for other plant diseases.